A promising mixed micellar approach to tune the oxidation of isoprenol by diperiodatoargentate(iii) in aqueous media. (3rd February 2023) - Kundu, Sandip; Karmakar, Priya; Rahaman, Sk Mehebub; Mitra, Mandira; Rajwar, Sangita; Dhibar, Subhendu; Layek, Mousumi; Sar, Pintu; Saha, Bidyut
Abstract : A green envelope of aqueous mixed micellar media composed of CPC and Brij-35 catalyzes the diperiodatoargentate(iii ) governed oxidation of isoprenol. Abstract : The use of environmentally benign nanoreactors in water is crucial for sustainable organic synthesis. Herein, we report that nanomicelles formulated by two surfactants (cationic cetylpyridinium chloride (CPC) and nonionic polyoxyethylene (23) lauryl ether (Brij-35)) in water produce efficient catalysis of diperiodatoargentate(iii ) directed oxidation of unsaturated alcohol, isoprenol. Interestingly, the maximum speed of reaction was observed when CPC and Brij-35 existed together in a 1 : 1 mole ratio. The kinetic outcome was elucidated with the help of 1 H NMR analysis and favourable micellization of the binary surfactant system. The various mixed micellar microenvironment influences the reaction rate following the confinement of reactants at close proximity to the micellar pseudophase. The reaction, performed through this green envelope of mixed micellar media, reduces the time of reaction effectively.